Letture geometriche delle architetture ecclesiali: fruizione virtuale attraverso la documentazione H-BIM - Lanzara, Emanuela (2018)
This contribution presents a research experience that deals with the geometric interpretation of the ovalshaped churches of the city of Naples starting from three-dimensional surveys, in order to implement projects of knowledge and communication with digital systems that favor the virtual fruition of the architectural heritage.